Análisis Financiero a la Cooperativa de Transportes Unión Yanzatza, Periodo 2021-2022 - Romero Tene, Fernanda Nicol (2024)
The purpose of the Curricular Integration Work entitled: Financial Analysis related to the Transportation Company “Unión Yanzatza”, period 2021-2022 is to evaluate the financial and operational performance of the company to facilitate decision making, through the application of vertical and horizontal analysis to the financial statements. In order to meet the established objectives, several methods were used to process the information gathered from the Transportation Company, including its financial statements, in order to understand the results obtained in the vertical analysis, which allows us to observe the participation of the accounts in a period, while the horizontal analysis examined the variations in the items of the financial statements between 2021 and 2022, thus allowing us to make evaluations based on the values obtained. The most appropriate methods were selected, starting with the scientific method, which made it possible to identify and classify the theoretical information essential for the development of the practice. Then, the deductive and inductive methods were used to advance from general concepts to particular or more significant aspects, drawing conclusions from the last mentioned. The mathematical method was used to calculate and visually represent the percentages relative to the different categories of accounts, as well as to solve the financial indicators that allow us to verify economic stability, measure the efficiency of investments and determine the capacity for financial autonomy. Likewise, the statistical method was applied to present these values in a way that would make them more accessible for analysis. Finally, the analytical and synthetic method was used to examine the cause and effect relationships in the data found and to provide relevant conclusions and recommendations in the report. This will facilitate decision making by the managers and administrators of the Transportation Company “Unión Yantzaza”, helping them to adopt the best measures for the future. The Financial Analysis concluded that the Cooperative has more Current Assets, which is beneficial because with the proper management of these assets it is possible to solve unforeseen events and generate income, it also has no Non-Current Liabilities or long-term debts and obligations, which shows a low level of indebtedness.